A mechanistic study of silver nanostructures incorporated reduced graphene oxide via flow synthesis approach - Lau, Kam Sheng; Tan, Sin Tee; Ginting, Riski Titian; Khiew, Poi Sim; Chin, Siew Xian; Chia, Chin Hua (Royal Society of Chemistry, 2020)
In situ growth of silver nanostructures (AgNSs) and reduction of graphene oxide (rGO) were successfully performed using a one-step segmented flow reaction system. The detailed crystal growth mechanism of the AgNSs on the rGO was discussed. The relationship between the presence of AgNSs (nanoparticles and nanowires) on the rGO and the rGO’s electrochemical behaviour was investigated. In this report, it was found that the presence of silver nanoparticles (AgNPs) on the rGO’s surface enhances its specific capacitance by 400% as compared to rGO-based devices. This novel finding provides an alternative in designing future electronic devices.